Endothelial cell rearrangements during vascular patterning require PI3-kinase-mediated inhibition of actomyosin contractility. Issue 1 (December 2018) - Angulo-Urarte, Ana; Casado, Pedro; Castillo, Sandra; Kobialka, Piotr; Kotini, Maria; Figueiredo, Ana; Castel, Pau; Rajeeve, Vinothini; Milà-Guasch, Maria; Millan, Jaime; Wiesner, Cora; Serra, Helena; et al.
Abstract Angiogenesis is a dynamic process relying on endothelial cell rearrangements within vascular tubes, yet the underlying mechanisms and functional relevance are poorly understood. Here we show that PI3Kα regulates endothelial cell rearrangements using a combination of a PI3Kα-selective inhibitor and endothelial-specific genetic deletion to abrogate PI3Kα activity during vessel development. Quantitative phosphoproteomics together with detailed cell biology analyses in vivo and in vitro reveal that PI3K signalling prevents NUAK1-dependent phosphorylation of the myosin phosphatase targeting-1 (MYPT1) protein, thereby allowing myosin light chain phosphatase (MLCP) activity and ultimately downregulating actomyosin contractility. Decreased PI3K activity enhances actomyosin contractility and impairs junctional remodelling and stabilization. This leads to overstretched endothelial cells that fail to anastomose properly and form aberrant superimposed layers within the vasculature. Our findings define the PI3K/NUAK1/MYPT1/MLCP axis as a critical pathway to regulate actomyosin contractility in endothelial cells, supporting vascular patterning and expansion through the control of cell rearrangement. Angiogenesis requires dynamic endothelial rearrangements and relative position changes within the vascular tubes. Here the authors show that a PI3K/NUAK1/MYPT1/MLCP pathway regulates actomyosin contractility in endothelial cells and cellular rearrangement during vascular patterning.